2016
DOI: 10.1038/tp.2016.120
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and epigenetic methylation defects and implication of the ERMN gene in autism spectrum disorders

Abstract: Autism spectrum disorders (ASD) are highly heritable and genetically complex conditions. Although highly penetrant mutations in multiple genes have been identified, they account for the etiology of <1/3 of cases. There is also strong evidence for environmental contribution to ASD, which can be mediated by still poorly explored epigenetic modifications. We searched for methylation changes on blood DNA of 53 male ASD patients and 757 healthy controls using a methylomic array (450K Illumina), correlated the varia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
23
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(25 citation statements)
references
References 79 publications
(89 reference statements)
0
23
0
2
Order By: Relevance
“…Epigenetic variation induced by non-genetic exposures has been hypothesized to be one mechanism by which environmental factors can affect risk for ASD [14,15]. Recent studies have provided initial evidence for autism-associated epigenetic variation in both brain and peripheral tissues [16][17][18][19][20][21], although these analyses have been undertaken on relatively small numbers of samples with limited statistical power. Existing analyses have assessed epigenetic variation in samples collected after a diagnosis of ASD has been assigned and are potentially confounded by factors such as smoking [22][23][24], medication [25,26], other environmental toxins [27] and reverse causation [28].…”
Section: Introductionmentioning
confidence: 99%
“…Epigenetic variation induced by non-genetic exposures has been hypothesized to be one mechanism by which environmental factors can affect risk for ASD [14,15]. Recent studies have provided initial evidence for autism-associated epigenetic variation in both brain and peripheral tissues [16][17][18][19][20][21], although these analyses have been undertaken on relatively small numbers of samples with limited statistical power. Existing analyses have assessed epigenetic variation in samples collected after a diagnosis of ASD has been assigned and are potentially confounded by factors such as smoking [22][23][24], medication [25,26], other environmental toxins [27] and reverse causation [28].…”
Section: Introductionmentioning
confidence: 99%
“…In a search for methylation changes on blood DNA of 53 male ASD patients and 757 healthy controls, Homs et al obtained 700 differentially methylated cytosine-guanine sites (CpGs) most of which were hypomethylated among the autistic patients (83.9%), with cisacting expression changes at 7.6% of locations, including (a) Hypomethylation induced by rare genetic variants (meSNVs), in spite of the notion that the disorder arises from common gene variants, at six loci (ERMN, USP24, METTL21C, PDE10A, STX16 and DBT) significantly associated with ASD (q-value <0.05); and (2) Clustered epimutations linked to transcriptional changes in single-Autism patients (n=4) [14,15]. All themeSNVs and clustered 'epi-mutations' were inherited from unaffected parents.…”
Section: Commentarymentioning
confidence: 99%
“…Lintas et al have shown that post-mortem analyses of autistic patients expressed markedly higher numbers of methylated CpG islands and greater methylation in the 5' region of the RELN gene promoter, spanning from -458 to -223 bp, whereas the compared control brains expressed more methylated CpG positions and greater extent of methylation at the 3' promoter region, spanning from -222 to +1 bp, with the upstream promoter region (-458 to -364 bp) showing methylation only in patients brains, whereas the most downstream region (-131 to +1 bp) was methylated exclusively in the control brains [13]. The authors concluded that the pattern of methylation differed between ASD patients' and the control brains, with ASD-specific CpG positions conferring risk through 'blunting' reelin gene expression.In a search for methylation changes on blood DNA of 53 male ASD patients and 757 healthy controls, Homs et al obtained 700 differentially methylated cytosine-guanine sites (CpGs) most of which were hypomethylated among the autistic patients (83.9%), with cisacting expression changes at 7.6% of locations, including (a) Hypomethylation induced by rare genetic variants (meSNVs), in spite of the notion that the disorder arises from common gene variants, at six loci (ERMN, USP24, METTL21C, PDE10A, STX16 and DBT) significantly associated with ASD (q-value <0.05); and (2) Clustered epimutations linked to transcriptional changes in single-Autism patients (n=4) [14,15]. All themeSNVs and clustered 'epi-mutations' were inherited from unaffected parents.…”
mentioning
confidence: 99%
“…Interactions between maternal immune system and epigenetic regulation in foetal brain is another theory of genesis of ASD phenotype. Epigenetic modifications and Methylation defects via environmental effects is also a suggested newer mechanism [13,29].…”
Section: Editorialmentioning
confidence: 99%
“…On the other hand, the recent studies have shown a broad allelic overlap between autism and higher intelligence which opens a newer way of approach to search of genetic causes [12]. However genetic mutations that are identified account only for less than one third of ASD cases [13].The rapid increase in numbers during last few decades supports a major role in environmental factors over genetic causes alone [14,31]. The other possibility is that the environmental factors may be contributing to activate the genetic or epigenetic mechanisms of development of autism.…”
mentioning
confidence: 99%